High rates of aggressive features in young Vietnamese females with papillary thyroid carcinoma: Associations with preoperative risk factors - Van De, Nguyen; Thi Huyen, Dao; Huu Tam, Dinh (Trends in Immunotherapy, 2024)
Background: Thyroid carcinoma represents a significant global health burden, rising worldwide incidence. Papillary thyroid carcinoma (PTC) accounts for most cases, but aggressive variants with capsular invasion and nodal metastases require more intensive treatment. Reported rates of these capsular invasion and cervical lymph node metastasis vary widely. This study aimed to elucidate associations between clinical/tumor characteristics, capsular invasion, and nodal metastasis in Vietnamese PTC patients. Methods: This retrospective cohort study examined 1626 patients with cytologically/histologically confirmed thyroid carcinoma at a referral center in Vietnam during 2018–2020. Data collected included demographics, imaging, cytology, tumor features, capsular invasion, and nodal metastasis. Associations were analyzed using chi-squared tests and binary logistic regression. Results: Most patients were young (≤ 45) females with small papillary carcinomas. High rates of capsular invasion (58.7%) and nodal metastasis (28.5%) were observed. Capsular invasion was associated with higher TIRADS categories, Bethesda cytological categories, larger tumors, and papillary histology. Nodal metastasis was linked to younger age, male sex, higher TIRADS categories, larger tumors, papillary histology, and capsular invasion. Binary logistic regression identified TIRADS categories, Bethesda cytological categories, larger tumor size, younger age, male sex, and capsular invasion as independent predictors. Conclusion: Unexpectedly high rates of capsular invasion and cervical lymph node metastasis were found. TIRADS, Bethesda system, tumor size, age, sex, and capsular invasion were significant preoperative risk factors for aggressive PTC behaviors.